Effect of tenofovir disoproxil fumarate on drug-resistant HBV clones. Issue 1 (January 2016) - Murakami, Eisuke; Tsuge, Masataka; Hiraga, Nobuhiko; Kan, Hiromi; Uchida, Takuro; Masaki, Keiichi; Nakahara, Takashi; Ono, Atsushi; Miki, Daiki; Kawaoka, Tomokazu; Abe, Hiromi; Imamura, Michio; et al.
Summary: Background & aims: Tenofovir disoproxil fumarate (TDF) has been approved for chronic hepatitis B treatment, and favorable susceptibility of hepatitis B virus (HBV) has been indicated. However, differences in TDF susceptibility among HBV genotypes and drug-resistant strains are unclear. In this study, TDF susceptibilities between genotypes A and C were evaluated in vitro and in vivo using several drug-resistant HBV clones. Methods: HBV expression plasmids were constructed from sera of HBV carriers, and drug-resistant substitutions were introduced by site-directed mutagenesis. TDF susceptibility was evaluated by changes of core-associated HBV replication intermediates in vitro or by change of serum HBV DNA in human hepatocyte chimeric mice carrying each HBV clone in vivo . Results: TDF susceptibilities of lamivudine-resistant clones (rtL180M/M204V) and lamivudine plus entecavir-resistant clones (rtL180M/S202G/M204V) were similar to wild type clones in vitro . However, lamivudine plus adefovir-resistant clones (rtA181T/N236T) acquired tolerance to TDF, and the rtN236T mutation was considered to be a causal substitution for TDF resistance. Furthermore, genotypic differences in TDF susceptibility were also observed between genotypes A and C in vitro, and the differences could be confirmed in vivo ( p = 0.023). Conclusions: The present study indicates that TDF susceptibility varies among HBV genotypes and drug-resistant HBV clones. Highlights: We compared tenofovir disoproxil fumarate (TDF) susceptibilities between HBV genotype A and C. N236T substitution in HBV RT region is significantly associated with TDF susceptibility. Genotypic differences in TDF susceptibility were observed between genotypes A and C in vitro and in vivo .